Is Sugarcane a Convenient Feedstock to Provide Ethanol to Oxygenate Gasolines in Mexico? A Process Simulation and Techno-Economic-Based Analysis - Aburto, Jorge; Martínez-Hernández, Elías (Frontiers in Energy Research, 2021)
Sugarcane is a major crop produced in many tropical countries including Mexico and has been the basis of a well-established agroindustry. However, the variation in market prices and health concerns over the consumption of sugar are challenging the economics and sustainability of sugarcane growers and mills. This paper presents a techno-economic assessment of using existing production capacity of sugarcane in Mexico and the correspondent Mexican sugarcane mills for producing ethanol as gasoline oxygenate, in comparison to the export of excess sugar production. Using the most recent statistics, we found out that the bioethanol potential is of 849,260,499 L/year which can cover for 100 % of the premium and magna gasoline demand in metropolitan area (MA) and 48% of premium gasoline in rest of the country areas (RoCA) at 5.8 % w/v blending (2.7% O2 w/v). This can be done by diverting the 20% sugar production excess to ethanol with the benefit of a higher gross netback of 308.3 USD/ton of sugarcane in comparison to 222.5 USD/ton of sugarcane when it is exported. Furthermore, a minimum ethanol selling price (MESP) of 0.5211 USD/L was estimated, showing that ethanol might be competitive against MTBE (0.50 USD/L FOB gulf price) as gasoline oxygenate agent. Decarbonizing gasoline in Mexico through the use of ethanol might allow the abatement of 5,766.8 kg CO2/day when 20% sugar is used. Concerning the under construction Dos Bocas refinery in Tabasco State, southern Mexico, ethanol blend at 5.8% in gasolines might but also contribute to the abatement of 6.1 % of CO2 emissions and the required sugarcane was estimated at 1 million tons per year . All this indicates that sugarcane has a great potential as a feedstock to produce first generation ethanol as a gasoline oxygenate agent in Mexico.